PERAN UNMISS (UNITED NATIONS MISSIONS IN SOUTH SUDAN) DALAM PEMBEBASAN TENTARA ANAK DI SUDAN SELATAN - Bobby Soemantri; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This researchis a diplomaticc and strategy political study which describes UNMISS role in the release of child soldiers in South Sudan. This research will focus on how UNMISS resolving about child soldiers in South Sudan. This study interesting because describe about the UNMISS role in South Sudan.UNMISS must make the conflict in South Sudan is free from using child soldiers.This is qualitative research which used descriptive methods, and collecting datas from some resources like books,journals, official publications and relevant websites. This paper used the pluralism perspective and International Organization Theory from Clive Archer. The object in this research is UNMISSan main actor in International Relations.The results of this study indicate that UNMISS carried out several programs to reduce the use of child soldiers in South Sudan. UNMISS as a Communicator reports to the United Nations to be able to tighten applicable international law regarding the use of international law. UNMISS as facilitator also cooperates with government and opposition soldiers to reduce the use of child soldiers UNMISS as motivator release the child soldiers and provide training for former child soldiers. Keywords: International Organizations, Pluralism, Conflict, Child Soldiers, UNMISS ( United Nation Mission South Sudan )